2009
DOI: 10.1002/hfm.20161
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and visual distractor decrement in older worker manual assembly task learning: Impact of spatial reasoning, field independence, and level of education

Abstract: This study examined the impact of age on manual assembly task learning in the presence of visual and auditory distracters. Manual assembly task learning (e.g., number of learning trials needed to obtain consistently accurate assembly and near asymptote performance times) was studied in men and women between 18 and 65 years of age. Higher spatial reasoning capabilities were associated with fewer trials to reach the learning criterion, faster manual assembly times, and material prophylaxis for the type of distra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Only two studies exclusively deal with cognitive performance of old workers. Both Schwerha, Wiker, and Jaraiedi (2007) and Wiker, Schwerha, and Jaraiedi (2009) investigated the impacts of age and years of formal education on learning a manual assembly task in the presence of visual and auditory distractors among 18-65 years old workers. It has been found that the oldest group of workers required significantly more trials to learn the task than the youngest one.…”
Section: Analysis and Evaluation Of Ageing Workers' Functional Capacimentioning
confidence: 99%
“…Only two studies exclusively deal with cognitive performance of old workers. Both Schwerha, Wiker, and Jaraiedi (2007) and Wiker, Schwerha, and Jaraiedi (2009) investigated the impacts of age and years of formal education on learning a manual assembly task in the presence of visual and auditory distractors among 18-65 years old workers. It has been found that the oldest group of workers required significantly more trials to learn the task than the youngest one.…”
Section: Analysis and Evaluation Of Ageing Workers' Functional Capacimentioning
confidence: 99%
“…Similar to cognition, FD/FI is also age-dependent. Cross-sectional studies have shown that older adults are more FD than younger adults (Blackburn, 1984; Schwartz & Karp, 1967; Wiker, Schwerha, & Jaraledi, 2009). To date, there has been no longitudinal study of FD/FI changes over one’s lifespan; hence, cohort effects should be considered in interpreting cross-sectional research results.…”
Section: Fd or Fi And Cognitive Agingmentioning
confidence: 99%
“…For elderly persons, slips and falls might be caused by the combination of age, pathology, and environmental hazards (Fleming & Pendergast, 1993). First of all, aging affects the physical faculties such as strength, vision, and reaction times (Wiker, Schwerha, & Jaraiedi, 2009). Aging also causes a number of pathologies (Collins & O'Sullivan, 2010), which often require medical treatment.…”
Section: Introductionmentioning
confidence: 99%